Dynamic imaging of the stomach by real-time ultrasound–a method for the study of gastric motility. Issue 7 (July 1980) - Holt, S; McDicken, W N; Anderson, T; Stewart, I C; Heading, R C
Abstract : The use of real-time ultrasonic imaging of the stomach for the study of gastric contractions in response to a liquid test meal is described. Gastric contractions in the pyloric antrum and distal body of the stomach were observed on closed circuit television, recorded on to cassette tape and also imaged on polaroid and ciné film. Gastric contractions were recorded from the pyloric antrum by longitudinal scanning in the lower epigastrium and reproducible motility tracings were obtained on a fibreoptic chart recorded. Intravenous metoclopramide enhanced the magnitude and frequency of antral movement, which was abolished by intravenous propantheline. Real-time ultrasonic imaging permits the non-invasive study of gastric contractions. It is safe, may be repeated as required, and provides a method for the study of the effect of drugs and disease states on gastric motility.